Association between life’s crucial 9 and severe abdominal aortic calcification in U.S. Adults: the mediating role of the systemic inflammatory response index - Tang, Kaifeng; Wang, Linping; Ye, Jinming; Yuan, Feng (Frontiers in Endocrinology, 2025)
BackgroundLife’s Crucial 9 (LC9) is an emerging cardiovascular health scoring system that incorporates Life’s Essential 8 (LE8) alongside mental health factors. However, its relationship with severe abdominal aortic calcification (SAAC) remains poorly understood.ObjectivesThe objective of this study is to investigate the relationship between LC9 scores and the incidence of SAAC in the US population.MethodsData from 2,323 participants were analyzed, originating from the 2013-2014 National Health and Nutrition Examination Survey (NHANES) cycle. In exploring the dynamics of LC9, its constituents, and their relationship with SAAC, we employed advanced statistical methodologies, specifically multivariable logistic regression and weighted quantile sum regression. Subgroup interaction analyses were conducted to reinforce the conclusions, and mediation analysis was employed to investigate how the systemic inflammatory response index (SIRI) influences the connection between LC9 and SAAC.ResultsIn fully adjusted models, an increase of 10 points in LC9 scores was associated with a 26% reduction in the prevalence of SAAC, achieving statistical significance (P < 0.001). As LC9 scores increased, a significant decline in SAAC prevalence was noted (P < 0.05). The WQS analysis pinpointed strong links between the occurrence of SAAC and variables including exposure to tobacco, blood pressure levels, blood glucose concentrations, and mental health status, the odds ratio stood at 0.244, with the 95% CI extending from 0.119 to 0.495. SIRI was positively correlated with SAAC (P < 0.05) and decreased with rising LC9 scores (β = -0.09, P < 0.001). Mediation analysis revealed that the SIRI significantly influenced the linkage between LC9 and SAAC, accounting for 5.8% of the mediation effect, with a statistically significant p-value (P < 0.001).ConclusionThis research highlights a robust inverse relationship between elevated LC9 scores and reduced SAAC incidence, suggesting the significant role of LC9 as a key factor in diminishing the frequency of SAAC. Furthermore, SIRI mediates this relationship.